2020
DOI: 10.13075/ijomeh.1896.01478
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic background and risk perception in construction workers: development and validation of an exploratory tool

Abstract: Objectives: Among occupational sectors, construction is still one of the branches with the highest reported numbers of work-related injuries and diseases, which can even lead to death and in many cases induce permanent health consequences. The vast majority of these occupational injuries and diseases are preventable; accordingly, an improvement in preventive strategies, also through a better knowledge of the main factors involved in these events, is one of the most important objectives for better occupational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…In addition to environmental pollution, studies have also documented that migrant construction workers’ health is affected by their socio-demographic characteristics, such as gender, age, ethnicity, education, income, working year, environmental literacy, and frequency of mass media usage [ 25 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. Therefore, the influences of these variables on migrant construction workers’ health were controlled.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to environmental pollution, studies have also documented that migrant construction workers’ health is affected by their socio-demographic characteristics, such as gender, age, ethnicity, education, income, working year, environmental literacy, and frequency of mass media usage [ 25 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. Therefore, the influences of these variables on migrant construction workers’ health were controlled.…”
Section: Methodsmentioning
confidence: 99%
“…As a classical factor to affect health, income was also tested. It has been shown that workers with low income tend to save money to support family, rather than spending money on health services for themselves [ 25 ]. Therefore, migrant construction workers with a lower income level may have a weaker sense of health, and worse health status compared with workers with higher income.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations